(untitled) (Journal of actual problems of jurisprudence, 2023)
One of the central tenants of Kazakhstani State policy is protecting and developing its labor potential, meeting both domestic and global community demands for workforce preservation. Successful developed nations follow one simple rule in regards to this matter – investing in human health preservation is both rewarding economically as well as socially; under EU-WTO Agreement mandate, hazards to life and health be assessed periodically and evaluated; this article describes valid approaches and regulatory regulations applicable when it comes to evaluating professional hazards. Our study utilized both general and specialized research methods. Its methodological framework consisted of using various legal analysis/synthesis/dialectic/social approaches; we combined all these forms of scientific investigation in order to demonstrate our study’s uniqueness while supporting its conclusions. Research results: modifications were proposed for methods for deciding whether or not to fund preventive and rehabilitation actions related to occupational hazards and types of economic activities. Kazakhstan needs to review their existing financing mechanisms of social insurance systems of industrial accidents to encourage employers in improving safety and working conditions within their enterprises. Proposed changes will serve to enlighten and support employers as they look towards strengthening workplace conditions for safety improvement. Key words: occupational hazard, type of economic activity, preventive and rehabilitation measures, occupational safety.